Hermeneutics of belief in San Augustine - Flórez Flórez, Alfonso (Estudios de Filosofía, 2002)
The complex relations that come about between believing and knowing and between knowing and believing, without it being possible to assign priority to any of such acts are considered here. This circle is fundamental for the constitution of human life, just as its enrooting shows it in language, a primordial gift, which makes the dynamics of a belief possible.